2016
DOI: 10.1021/acs.joc.5b02487
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted Formal [4 + 3] Annulation between 2-Fluorophenylacetylenes and Ketones: A Route to Benzoxepines

Abstract: The first base-promoted formal [4 + 3] annulation between 2-fluorophenylacetylenes and ketones has been disclosed. The reaction proceeds through a tandem α-vinylation of ketones followed by an intramolecular nucleophilic aromatic substitution (SNAr) reaction of the in situ generated β,γ-unsaturated ketone intermediates, providing a straightforward access to a wide range of functionalized benzoxepines in moderate to high yields. The transition-metal-free methodology featured a wide substrate scope, the use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The presence of the BiPh 2 -moieties in 7 influences dramatically the backbone, increasing its torsion [C5–C7–C8: 108.8(3)°, C9–C8–C7: 115.0(3)° of 7 ] compared to non-substituted benzoxepine derivative [C5–C7–C8: 113.54°, C9–C8–C7: 118.20°]. 17 We attribute this high structural torsion to the steric constraint between both bismuth centers, resulting in a longer C1–C12 distance [4.324(1) Å of 7 vs. 4.039 Å of benzoxepine derivative]. However, the most remarkable feature in 7 is a Bi⋯Bi distance of 3.807(1) Å: much below the sum of the van der Waal radius (4.14 Å) and among the shortest distances between two Bi( iii ) atoms reported.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the BiPh 2 -moieties in 7 influences dramatically the backbone, increasing its torsion [C5–C7–C8: 108.8(3)°, C9–C8–C7: 115.0(3)° of 7 ] compared to non-substituted benzoxepine derivative [C5–C7–C8: 113.54°, C9–C8–C7: 118.20°]. 17 We attribute this high structural torsion to the steric constraint between both bismuth centers, resulting in a longer C1–C12 distance [4.324(1) Å of 7 vs. 4.039 Å of benzoxepine derivative]. However, the most remarkable feature in 7 is a Bi⋯Bi distance of 3.807(1) Å: much below the sum of the van der Waal radius (4.14 Å) and among the shortest distances between two Bi( iii ) atoms reported.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that KOt-Bu plays an important role to improve the yield of 2-aminoethyl acetate product from this ring-opening N-alkylation. Then, when this reaction is performed in a mixed solvent system (DMC/H 2 O 8:2), only 40% yield of the desired product 3a was produced, while no labeled compound was detected by GC-MS in the 18 O-labeled experiment (Scheme 7b and c). These important results revealed that the oxygen of product 3a does not come from water or air, and it may be transferred from KOt-Bu as supported by Dash and co-worker who demonstrated KOt-Bu can serve as an oxygen source [26].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, potassium tert-butoxide has been shown to be an efficient promoter for C-C-bond formation reactions [18][19][20][21][22]. However, only few reports described C-N-bond cross-coupling reactions using potassium tert-butoxide as promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Qi and Jiang used t-BuOK in their (4+3)-annulation to furnish benzoxepines 2.19c from 2-fluorophenylacetylenes 2.19a and ketones 2.19b (Scheme 2.19). 41 The reaction tolerated various alkyl (hetero)aromatic and (cyclo)aliphatic ketones, though steric effects constituted an important limitation in the case of alkyl benzyl ketones. As for the 2-fluorophenylacetylenes, good to excellent yields were obtained whether the aromatic ring was electron-rich or poor.…”
Section: Special Topic Synthesismentioning
confidence: 99%